A Performance Centred Competency Based Approach to Quality University Teaching - Cejas Martínez, M.F. (2019)
In order to encourage more flexible working environments and establish generators of sustainable development for participating countries through an educated society, various international organisations that intervene in the quality dimension within the framework of a systemic approach to Higher Education, including the World Bank, have made multiple efforts to establish various recognitions, certifications and credits pertaining to competency-based education.